2018
DOI: 10.1002/ejp.1179
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Persistent socio‐economic inequality in frequent headache among Danish adolescents from 1991 to 2014

Abstract: The prevalence of frequent headache among adolescents increases with decreasing SES. This socio-economic inequality has been persistent among adolescents in Denmark from 1991 to 2014. Clinicians should be aware of this social inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In view of the significant gender differences in pain prevalence, researchers have suggested that gender may be an explanatory factor for pain [ 2 , 3 , 14 , 34 ]. It has been suggested that gender differences in pain prevalence may be explained by the interaction of different factors such as; biological factors, including hormones, psychological factors, such as anxiety and negative affect, and sociocultural factors, including gender role expectations of pain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the significant gender differences in pain prevalence, researchers have suggested that gender may be an explanatory factor for pain [ 2 , 3 , 14 , 34 ]. It has been suggested that gender differences in pain prevalence may be explained by the interaction of different factors such as; biological factors, including hormones, psychological factors, such as anxiety and negative affect, and sociocultural factors, including gender role expectations of pain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, the correlation of economic inequality and frequent headache was investigated in 31,102 adolescents of 11 to 15 years between 1991 and 2014 [22]. Overall, 10.4% of adolescents reported frequent headache.…”
Section: Recent Studies On Headache Prevalencementioning
confidence: 99%
“…Previous studies have shown that headache prevalence increases as socioeconomic status decreases 28,29 . This pattern is common to many diseases and a higher socioeconomic status is thought to be protective of headache [30][31][32][33][34][35][36][37][38] . We found no indication that being headache free is more prevalent in persons with higher socioeconomic status, high income, higher level of education or employment status.…”
Section: Discussionmentioning
confidence: 99%